Design, Oppression, and Liberation - Frederick van Amstel; Lesley-Ann Noel; Rodrigo Freese Gonzatto (Diseña, 2022)
The role of design in structuring oppression has gone largely unacknowledged by design research and design history. However, we can see a recent move, pushed by social movements, to recognize design’s complicity with many forms of oppression. Acknowledging oppressive design opens up the possibility of occupying, reclaiming, repairing, and restoring what oppressors have done with it. Some approaches shift design research from denouncing to announcing new realities. Without doing so, fatalism could prevail, even if critical of the current reality. In the case of design, this means putting equal effort on analyzing oppressive designs and on developing liberating designs. In tune with this implication, this special issue highlights research that contributes to both sharpening the understanding of oppression in design, and increasing the solidarity between the different struggles for liberation that cut across design.